Analysis of the joint angules of the throwing arm in javelin throw - Wang, Z. F.; He, W. J.; He, W. G. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to explore the feasibility of using the panning method to analyze the joint angles of the throwing arm during the throwing of javelin. Two cameras (250 Hz) were set on the side and the back of the runway to analyze the athlete`s throwing arm movemen with a panning method. Besides the joint angles of the shoulder (horizontal abduction/ horizontal adduction, abduction/ adduction, internal rotation/external rotation) and the elbow (extension/ flexion), the pronation/supination angles of the forearm, the ulnar/ radial flexion and the palmar flexion/ dorsiflexion of the wrist were also calculated . For each angle of the joints of the same trail of an athlete, the ICC (Intravlass correlation coefficients) of the two results from two different analysisers was bigger than 0.95 (P<0.01).